The linguistic competence of deaf primary school children - Griffiths, Amanda (1983)
Observation of deaf children in conversation with their teachers might lead one to believe they are behaving in a somewhat contrived way in comparison with their behaviour when communicating with their peers. Examination of the performance of deaf and hearing children on various reading tests has shown the deaf to be pursuing markedly different strategies from the hearing (e.g. word association). Such observations lead us to ask, is the linguistic behaviour of these children then simply a selection of 'special tricks' developed to cope with everyday demands? Or, if various measures of their language intercorrelate, can we assume the existence of a unitary linguistic competence?